Alternative and Complementary Therapies against Foodborne Salmonella Infections - Mohamed F. Ghaly; Zahraa M. Nasr; Amira I. Abousaty; Hanan G. Seadawy; Mohamed A. A. Shaheen; Sarah Albogami; Mohammad M. Al-Sanea; Mahmoud M. Bendary (MDPI AG, 2021)
The limitations in the therapeutic options for foodborne pathogens lead to treatments failure, especially for multidrug-resistant (MDR) Salmonella sp., worldwide. Therefore, we aimed to find alternative and complementary therapies against these resistant foodborne pathogens. Out of 100 meat products samples, the prevalence rate of salmonella was 6%, serotyped only as S. Typhimurium and S. Enteritidis. According to the antibiotic susceptibility assays, the majority of our isolates were MDR and susceptible to cefotaxime. Out of the 13 tested plant extracts, five only showed an inhibition zone in the range of 8-50 mm against both serotypes. Based on their promising activity, the oily extract of cinnamon and aqueous extract of paprika represented the highest potency. Surprisingly, a significant synergistic effect was detected between cinnamon oil and cefotaxime. Depending on Gas Chromatography/Mass Spectrometry (GC-MS), the antimicrobial activity of cinnamon oil was attributed to four components including linalool, camphor, (Z)-3-Phenylacrylaldehyde and its stereoisomer 2-Propenal-3-phenyl. The anti-virulence activities of these compounds were confirmed on the basis of computational molecular docking studies. Accordingly, we recommended the use of cinnamon oil as a food additive to fight the resistant foodborne pathogens. Additionally, we confirmed its therapeutic uses, especially when co-administrated with other antimicrobial agents.